Developmental Peculiarities and Seed-Borne Endophytes in Quinoa: Omnipresent, Robust Bacilli Contribute to Plant Fitness - Pitzschke, Andrea (Frontiers in Microbiology, 2016)
Among potential climate change-adapted crops for future agriculture, quinoa (Chenopodium quinoa), a facultative halophyte plant with exceptional nutritional properties, stands out as a prime candidate. This work examined how quinoa deals with extreme situations during seed rehydration. Quinoa distinguishes itself from other plants in multiple ways. It germinates within minutes, even under extremely hostile conditions. Broken seeds/split embryos are able to regenerate. Furthermore, quinoa seedlings are resurrection-competent. These peculiarities became in part explainable upon discovery of seed-borne microorganisms. 100% of quinoa seeds, from different sources, are inhabited by diverse members of the genus Bacillus. These endophytes are motile and reside in all seedling organs, indicating vertical transmission. Owing to their high catalase activities and superoxide contents the bacteria potentially manipulate the host’s redox status. Superoxide-driven cell expansion enables quinoa to overcome a critical period in development, seedling establishment. Quinoa’s immediate confrontation with “foreign” reactive oxygen species and bacterial elicitors likely induces a naturally primed state, enabling plants to withstand extreme situations. The endophytic bacteria, which are cultivable and highly robust themselves, have high potential for application in agriculture, food (amylase) and cosmetics (catalase) industry. This work also discusses the potential of transferring quinoa’s microbiome to improve stress resistance in other plant species.